AWARENESS ABOUT REGENERATIVE THERAPY WITH OF PLATELET RICH PLASMA (PRP) AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Platelet-rich plasma (PRP), serving as a vehicle and wellspring of development factors, is an homologous plasma formulation with congregated platelets broadly studied for its applications as a bioactive scaffold in cell-based intervention and tissue engineering . The aim of the study was to assess the awareness about regenerative therapy with platelet-rich plasma (PRP) among dental students. A cross-sectional study was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed the awareness about PRP regenerative therapy in surgical applications, their endodontic uses, periodontal applications, implant surgical applications, and bone healing. The responses were recorded and analyzed. 82% of the respondents were aware of surgical applications of PRP regenerative therapy . 73% were aware of endodontic uses of regenerative therapy . 77% of the respondents were aware of periodontal applications of PRP regenerative therapy . 75% of the respondents were aware of implant surgical applications of PRP regenerative therapy. 78 % of the respondents were aware of the bone healing properties of PRP regenerative therapy . The awareness about the use of PRP regenerative therapy in dental applications is high among dental students. Increased awareness programs and sensitization and continuing dental education programs, along with greater importance to the curricular modifications, can further enhance knowledge and awareness about PRP regenerative therapy.